Full disclosure ebook - Henderson, Dee (2012)
Midwest Homicide Investigator Ann Silver appears out of nowhere and drops the best lead on a serial murder case that Special Agent Paul Falcon has had in years. But is he ready for this case's secrets—or this woman's?